1996
DOI: 10.1088/0264-9381/13/3/008
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic theory for particle production

Abstract: Recently, the phenomenological description of cosmological particle production processes in terms of effective viscous pressures has attracted some attention. Using a simple creation rate model we discuss the question to what extent this approach is compatible with the kinetic theory of a relativistic gas. We find the effective viscous pressure approach to be consistent with this model for homogeneous spacetimes but not for inhomogeneous ones.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
0
3

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(73 citation statements)
references
References 22 publications
(56 reference statements)
3
67
0
3
Order By: Relevance
“…The first attempt to incorporate gravitational particle production was discussed long ago by Triginer, Zimdahl and Pavón [28]. Following these authors we starting by writing the modified Boltzmann equation in the form:…”
Section: A the Kinetic Non-collisional Termmentioning
confidence: 99%
“…The first attempt to incorporate gravitational particle production was discussed long ago by Triginer, Zimdahl and Pavón [28]. Following these authors we starting by writing the modified Boltzmann equation in the form:…”
Section: A the Kinetic Non-collisional Termmentioning
confidence: 99%
“…Particle production within the framework of kinetic theory can be incorporated as a viscous pressure. It has been shown that the inclusion of particle production, in a general relativistic background, leads to a kinetic equation of the form [54] …”
Section: Solutions To the Boltzmann Equation And Foam-modified Thementioning
confidence: 99%
“…In a similar manner to particle creation cases [16] in imperfect fluids [17,18], the highly nontrivial time-dependence of the mode p H and the transfer of energy between regions, due to the defrosting of this mode across the boundary p H , gives rise to pressure corrections in the fluid energy conservation law. The defrosting of the modes results in a time-dependent "particle number" for regions near p H .…”
Section: Analytical Expression For T µνmentioning
confidence: 92%
“…The defrosting of the modes results in a time-dependent "particle number" for regions near p H . From kinetic theory we know that this "particle creation", (the defrosting of the modes), gives rise to effective viscous pressure modifications [17,18]. The term Π i denotes the effective viscous pressure modification to the "bare" pressure, p i .…”
Section: Analytical Expression For T µνmentioning
confidence: 99%